Six new bacterial species of Marinilabiliales isolated from the marine coastal sediment and reclassified Ancylomarina and Labilibaculum as Marinifilum comb. nov. based on the genome analysis - Zhang, Han-Zhe; Teng, Jin-Hao; Zhou, Hao-Yu; Liu, Tian-He; Lu, De-Chen; Du, Zong-Jun (Frontiers in Microbiology, 2025)
Evaluation of bacterial succession with cultivation-dependent strategies during enrichment culturing marine sediment led to the isolation of six strains that affiliated with the order Marinilabiliales. Six strains were selected for a taxonomic study after discarding clonal cultures. A thorough phylogenetic, genomic and phenotypic analysis of the isolates indicated that they represented six new species. Molecular data revealed the existence of an as yet uncultivated novel species recurrently binned from the enrichment culturing metagenomes. Using a combination of genomic, phylogenetic, and biochemical approaches, we characterized six novel Marinilabiliales species capable of degrading marine macroalgal polysaccharides. Bioinformatic polysaccharide utilization loci (PUL) annotations suggest usage of a large array of polysaccharides, including laminarin, α-glucans, and alginate as well as mannans and fucans, highlighting the genus’ involvement in the marine carbon cycle. This study represented a new example of the use of the tandem approach of whole cell mass spectrometry linked to 16S rRNA gene sequencing in order to facilitate the discovery of new taxa by high-throughput cultivation, which increases the probability of finding more than a single isolate for new species. Analysis of CAZymes genes and PUL counts revealed substantial potential for polysaccharide utilization of Marinilabiliales. The taxonomic study resulted in the classification of six new species and reclassified Ancylomarina and Labilibaculum as Marinifilum of the order Marinilabiliales for which we propose the names Carboxylicivirga agarovorans sp. nov., Carboxylicivirga longa sp. nov., Carboxylicivirga caseinilyticus sp. nov., Carboxylicivirga litoralis sp. nov., Carboxylicivirga fragile sp. nov., and Marinifilum sediminis sp. nov.